Manual Removal of the Placenta after Vaginal Delivery: An Unsolved Problem in Obstetrics. (9th April 2014) - Urner, Fiona; Zimmermann, Roland; Krafft, Alexander
Abstract : The third stage of labor is associated with considerable maternal morbidity and mortality. The major complication is postpartum hemorrhage (PPH), which is the leading cause of maternal morbidity and mortality worldwide. Whereas in the event of PPH due to atony of the uterus there exist numerous treatment guidelines; for the management of retained placenta the general consensus is more difficult to establish. Active management of the third stage of labour is generally accepted as standard of care as already its duration is contributing to the risk of PPH. Despite scant evidence it is commonly advised that if the placenta has not been expelled 30 minutes after delivery, manual removal of the placenta should be carried out under anaesthesia. Pathologic adhesion of the placenta in the low risk situation usually is diagnosed at the time of delivery; therefore a pre- or intrapartum screening opportunity for placenta accreta would be desirable. But diagnosis of abnormalities of placentation other than placenta previa remains a challenge. Nevertheless the use of ultrasound and doppler sonography might be helpful in the third stage of labor. An improvement might be the implementation of standardized operating procedures for retained placenta which could contribute to a reduction of maternal morbidity.